Factors Influencing Mitigation of Risk of Waterborne Disease in Vietnam Among Small Scale Integrated Livestock Farmers - Hall, David C.; Le, Quynh B. (Frontiers in Veterinary Science, 2018)
The integrated livestock, crops, and fish (VAC) model of integrated small scale agriculture has been important to economic and ecological sustainability in Vietnam for many centuries. Recently, emerging waterborne diseases including avian influenza as well as the potential for zoonotic disease arising from small scale farms have jeopardized the VAC model. In order to promote mitigation of the risk of waterborne and other diseases in the VAC system, there needs to be recognition of the significant predictors of such behavior, particularly with respect to water sources including well and rain water. We report primarily quantitative results of research generated from 300 farms in each of North and South Vietnam that indicate the small scale farmers who are more likely to engage in mitigation of waterborne disease are those who raise pigs, perceive themselves to be more at risk of HPAI infection from well water, report they are good livestock managers, value the advice of health care workers, and where a female household member is the decision maker for family health. These results bear importance to water and health policy formulators in rural Vietnam. (JEL I130, I180, O130, Q180, Q570). JEL CLASSIFICATIONS: I130: Health and economic development I180: Public health O130: Economic Development: Agriculture; Environment Q180: Agricultural policy; Food policy Q570: Ecological economics: biodiversity conservation